Total probabilistic measure for the potential risk of regional roads exposed to landslides. (December 2022) - Liu, Qiang; Tang, Aiping; Huang, Delong; Huang, Ziyuan; Zhang, Bin; Xu, Xiuchen
Highlights: Time probability model obtained is a time conditional probability with space and magnitude as parameters and time as the variable. Road vulnerability decreases with the increase of road resistance while increasing with the increase of landslide intensity. Outcomes of road risk at different scales and time periods facilitate multi-level risk management in different periods. Abstract: This paper presents a probabilistic analysis of the landslide risk encountered by regional roads, and the landslide risk of roads is regarded as a function of landslide hazard and road vulnerability. First, a hazard model considering the interdependence of time, space, and the magnitude of landslides was developed to express the landslide probability. Meanwhile, a probabilistic landslide vulnerability was introduced into the road vulnerability to show the vulnerable locations, damage states, and the damage probabilities of the road. Finally, the road risk exposed to landslides was formulated as the product of hazard and vulnerability. Results show that the probability of the regional road reaching a specific damage state varies with the time interval, landslide scale, and spatial location. Geographically, the Mudanjiang-Suifenhe line maintains a high-risk level; while, in terms of the risk evolution in time and scale, the maximum value of failure probability faced by the road network is 0.047, 0.364, and 0.603 for small-scale, medium-scale, and large-scale landslides in the next 10 years; and 0.049, 0.467, and 0.618 for small-scale, medium-scale, and large-scale landslides in the next 30 years. This study provides guidance for the hierarchical management and prevention of disaster risk for regional roads in different periods.